Spontaneous Agglomeration of Fluorinated Janus Particles and Its Effect on the Adsorption Behavior of Oil-Air Surfaces - Li, Gen; Wang, Keliang; Lu, Chunjing (Frontiers in Chemistry, 2021)
Based on the Pickering emulsion template method, two types of Janus particles with different relative amphiphilic areas for stabilizing non-aqueous foam were synthesized. In addition, particles with uniformly modified surface were synthesized for comparison. By adjusting oil mixtures, the behavior of particles on the oil-air surface was measured. Moreover, the role of particle agglomerates in surface adsorption process was investigated. Affected by the particle surface contact angle, the surface activity of Janus particles is not always greater than that of uniformly modified particles, which is reflected on delta surface tension and the volume of foam generated. The oil-surface adsorption process of synthesized Janus particles is not only occurred in the form of independent detached particles, but also in the form of particle agglomerates. The adsorption of the particles from the bulk phase to the surface requires the contact angle of the Cassie-Baxter composite surface of the particle agglomerates to be around 90°, but the inherent contact angle of the individual particles is less than 90°.